2008
DOI: 10.1089/end.2008.9709
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-Month Results of a Randomized Prospective Study Comparing Transurethral Photoselective Vaporization with Transvesical Open Enucleation for Prostatic Adenomas Greater Than 80 cc

Abstract: Our results indicate that for an 18 month period photoselective vaporization of the prostate is a highly acceptable treatment alternative to open prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 19 publications
1
47
0
13
Order By: Relevance
“…In our study, only 4 (13.3%) patients had a prostate volume greater than 80 mL, but we did not see any difference in efficacy or reoperation rate. Similar results were reported by Skolarikos et al, [15] who compared PVP to open prostatectomy for large prostatic adenomas (>80 mL), indicating that PVP is an acceptable treatment alternative to open surgery.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, only 4 (13.3%) patients had a prostate volume greater than 80 mL, but we did not see any difference in efficacy or reoperation rate. Similar results were reported by Skolarikos et al, [15] who compared PVP to open prostatectomy for large prostatic adenomas (>80 mL), indicating that PVP is an acceptable treatment alternative to open surgery.…”
Section: Discussionsupporting
confidence: 86%
“…The relatively shorter catheterization time and lower delivered energy in our series may be related to this condition. Efficacy of PVP on BPH was shown in many studies [18,19,20,21]. In a recently published first study investigating 80 W PVP in CaP patients with BOO, Jin et al reported perfect safety and satisfying functional outcomes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Başarı ve Komplikasyonlar: Açık prostatektomi sonrası AUSS' deki düzelme %63-86, IPSS'deki düzelme %60-87, postvoiding rezidü idrar miktarındaki azalma %86-98 olarak bildirilmiştir. Re-operasyon oranları yok denecek kadar azdır [11][12][13][14][15]. Açık prostatektomiye bağlı aşırı kanama eskiden büyük bir problem iken, modern cerrahi tekniklerle günümüzde kan kaybı çok azdır.…”
Section: Endikasyon Ve Kontrendikasyolarunclassified